(untitled) (Research, Society and Development, 2021)
Digital advances have changed the teaching-learning process. With this in mind, there was a proposal to describe the use of the Google Forms platform as a research method and verify its effectiveness in the pre and post contact of the remote activity. The league’s first online class held during the quarantine period had a total of 88 participants. 77 undergraduate students (87.5%), 02 graduate students (2.27%), and 09 professionals (10.23%). It is assumed that the predominance of undergraduates is due to the greater offer of undergraduate courses on campus, since 54 listeners (61.36%) belonged to the institution that promoted the event. Of the participants (71.95%), 59 people said they had never had contact with the indigenous population. Thus, the application of these forms can guide the real needs of the participants, and the league, in its educational character, promotes environments for learning in health. Concluding that in view of the pandemic scenario in which agglomerations should be avoided, with regard to the possibility of exploring diversified topics through the use of technological resources, this methodology of the Google Forms platform is an effective instrument for planning actions, whether teaching and /or health.